Optimizing Pulmonary Outcomes After Total Laryngectomy: Crossover Study on New Heat and Moisture Exchangers. (December 2022) - Longobardi, Ylenia; Galli, Jacopo; Di Cesare, Tiziana; D'Alatri, Lucia; Settimi, Stefano; Mele, Dario; Bussu, Francesco; Parrilla, Claudio
Objective: To evaluate the effects of new devices—heat and moisture exchangers (HMEs) and adhesives—on pulmonary symptoms, subject adherence, quality of life, dermatologic symptoms, and patient satisfaction after laryngectomy. Study Design: Prospective crossover study. Setting: Between December 2020 and April 2021, 40 patients were enrolled who had undergone laryngectomy, routinely used HMEs and adhesive, and were followed in our Department of Otolaryngology–Head and Neck Surgery. Methods: Patients were allocated into group A (new products) or group B (usual care) for 6 weeks. Then the 2 groups reversed, and each patient acted as his or her own control. Patients kept a diary and cough tally sheet. At baseline and after each 6-week period, 2 questionnaires were administered: EQ-5D (European Quality of Life–5 Dimensions) and CASA-Q (Cough and Sputum Assessment Questionnaire). Results: Six weeks of using new products resulted in the following effects for both groups: (1) a significant reduction in daily forced expectoration and dry coughs, (2) a significant improvement in all domains of the CASA-Q, (3) an increase in adherence to HME use, (4) a significant reduction in shortness of breath and skin irritation, and (5) significantly better scores in the anxiety/depression domain of the EQ-5D. Conclusion: Achieving this reduction in patients who were already highly adherent to HME use is clinically relevant and underscores the importance of using better-performing HMEs that can compensate for the humidification deficit. Improving pulmonary symptomatology could reduce patient restrictions in daily life and avoidance of social activity, with a consequent positive effect on quality of life.